An Evaluation On Speaking Exercises Of CommunicativeAnd Interactive English For Junior High School Based On Curriculum Used In SMP 18 Malang - Vidyasari, Aryuni, Drs. Djoko Srijono, M.Hum, Nur Hidayat Spd (2013)
The objective of this study is to evaluate the suitability of Speaking Exercise in English textbook with School Based Curriculum of SMP 18 Malang. The writer uses a documentary analysis as the method of collecting data. The data are taken from Communicative and Interactive English for the Second Grade of Junior High School, written by Drs. Otong Setiawan Djuharie, M.Pd and published by Yrama Widya .and analyzed by comparing speaking materials in the textbook with speaking materials in the School Based Curriculum. The results of this research paper show that 13 indicators out of 21 indicators match to the exercises.And percentage matching indicator for this book is 61,9 % . This percentage is good according to the schema of quality classification of Suharsimi , that states Interval Percentage 56-75 % is good.